2019
DOI: 10.1002/anie.201903014
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry, Biology, and Modulation of Ammonium Nitrification in Soil

Abstract: Approximately two percent of the world's energy is consumed in the production of ammonia from hydrogen and nitrogen gas. Ammonia is used as a fertilizer ingredient for agriculture and distributed in the environment on an enormous scale to promote crop growth in intensive farming. Only 30–50 % of the nitrogen applied is assimilated by crop plants; the remaining 50–70 % goes into biological processes such as nitrification by microbial metabolism in the soil. This leads to an imbalance in the global nitrogen cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 123 publications
0
36
0
Order By: Relevance
“…Biological nitrification inhibition (BNI) shows great potential as a component of sustainable agriculture because it uses the natural nitrification inhibitory potential of field crops (Coskun et al 2017;Subbarao et al 2013b;Subbarao and Searchinger 2021;Wendeborn 2020). BNI is a specific ecological phenomenon that occurs in the plant rhizosphere, where secondary metabolites emitted from plant roots inhibit nitrification of nitrifying microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Biological nitrification inhibition (BNI) shows great potential as a component of sustainable agriculture because it uses the natural nitrification inhibitory potential of field crops (Coskun et al 2017;Subbarao et al 2013b;Subbarao and Searchinger 2021;Wendeborn 2020). BNI is a specific ecological phenomenon that occurs in the plant rhizosphere, where secondary metabolites emitted from plant roots inhibit nitrification of nitrifying microbes.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic process of nitrification can be divided into three pathways: NH 3 oxidation pathway, NH 2 OH oxidation pathway, and NO 2 oxidation pathway. The enzymatic process is carried out by an electron transport chain and the reaction is exergonic (a biochemical reaction that releases energy) (Wendeborn, 2019). Ammonia monooxygenase (AMO) turns ammonia into NH 2 OH with the gain of two electrons (Daims et al, 2015).…”
Section: Electron Transport Chainmentioning
confidence: 99%
“…It is estimated a world nitrogen (N) fertilizer demand of around 110.000 thousand tonnes N for 2020 (FAO 2017) . Industrial N fixation to produce ammonium (NH 4 + ) fertilizers accounts for approximately two percent of the world's energy consumption (Wendeborn 2019). But crops use fertilizer N inefficiently as more than 50 % of its N is not assimilated by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Once checked enough BNI activity on Nitrosomona s sp. in pure cultures, it is necessary to test the effectiveness in the field (Wendeborn 2019). Lu et al (2019) found that 1,9-decanediol decreased AOB and AOA abundance in three different soils and changed AOB community structure.…”
Section: Introductionmentioning
confidence: 99%